2012
DOI: 10.1155/2012/832059
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effects of Docetaxel and Doxorubicin in Hormone-Refractory Prostate Cancer Cells

Abstract: Combination effects of docetaxel (DOC) and doxorubicin (DOX) were investigated in prostate cancer cells (PC3 and DU145). Combination indices (CIs) were determined using the unified theory in various concentrations and mixing ratios (synergy: CI < 0.9, additivity: 0.9 < CI < 1.1, and antagonism: CI > 1.1). DOC showed a biphasic cytotoxicity pattern with the half maximal inhibitory concentration (IC50) at the picomolar range for PC3 (0.598 nM) and DU145 (0.469 nM), following 72 h drug exposure. The IC50s of DOX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 64 publications
7
51
0
Order By: Relevance
“…Altogether, the results from MTT assays, cell cycle analysis, mitochondrial membrane potential analysis and apoptosis analysis provide strong support to the idea that CET MAb conjugation could improve the therapeutic potential of Nps for EGFR +ve cancers. [52][53][54][55] …”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the results from MTT assays, cell cycle analysis, mitochondrial membrane potential analysis and apoptosis analysis provide strong support to the idea that CET MAb conjugation could improve the therapeutic potential of Nps for EGFR +ve cancers. [52][53][54][55] …”
Section: Discussionmentioning
confidence: 99%
“…When we compared the cytotoxic activity of Teucrium persicum with that of some known anti-cancer drugs, we found that the IC 50 value of Teucrium persicum extract for PC-3 cells was much lower. The IC 50 values reported for doxorubicin, imatinib and etoposide against PC-3 cells are 500, 5700 and 1730 μg/ml respectively (Kubler et al, 2005;Dudley et al, 2008;Tsakalozou et al, 2012) which are much higher than that of Teucrium persicum extract (142μg/ml).…”
Section: Discussionmentioning
confidence: 78%
“…58,59 Hermandez-Vargas et al 59 were following changes in cell death, cell cycle, and gene transcription in MCF-7 and MDA-MB-231 breast cancer cell lines aer treatment with docetaxel. Their results revealed that docetaxel targeted different phases of cell cycle according to drug concentration, whereas a biphasic growth-response curve was in consistence with the existence of at least two different mechanisms of docetaxel's activity.…”
Section: -57mentioning
confidence: 99%
“…Later on, another group of authors concluded that biphasic doseresponse gained aer treatment of prostate cancer cell lines with docetaxel was occurred due to mitotic catastrophe at low concentrations, while apoptosis was the cause of cell death at concentrations higher than 10 mM. 58 Additionally, Szomolay and Shahrezaei 55 proposed a model where alterations in phosphorylation-dephosphorylation cycles due to different speeds of phosphatase and kinase activity can result in a variety of doseresponse behaviors.…”
Section: -57mentioning
confidence: 99%